Impact of Blended Learning on Student Learning Result in Microeconomics Course - Handayani, Sri (Classroom Action Research Journal (CARJO), 2018)
Improving the quality of education in Indonesia is done continuously and continuously. A quality learning process that is a process of communicative interaction between learners with teachers/lecturers. To make good learning interaction hence there is some component that is learning competence, learning method, learning material, classroom management, source/instructional media, assessment of learning and development of learning process. Therefore, for the learning process can be done properly there needs to be an innovation in the implementation of learning. By leveraging various learning resources and with the current technological sophistication of learning innovation is beginning to lead to Blended Learning-Based Learning (PBBL). Blended Learning-Based Learning combines the advantages of learning through three main learning sources, namely learning: (1) face-to-face; (2) offline; and (3) online. This research was conducted on the students of the participants of the Microeconomics course at the Faculty of Economics, State University of Malang. The type of research used in this research is Classroom Action Research (CAR). From the result of research indicate that the average of pre-test value (Cycle I) that is equal to 75,17 and 87,75 for cycle II. From the data, it can be seen that percentage of classical completeness in cycle I is still not reached 85%. However, the increase has been better 72.41% in cycle II and showed that the class activity in microeconomic subject students using Blended Learning has created active learning conditions in the classroom.Keywords:Â blended learning, learning result, microeconomics course